DYNAMICAL SYSTEM FOR EBOLA OUTBREAK WITHIN QUARANTINE AND VACCINATION TREATMENTS - Nurwijaya, Sugian; MA, Ratnah Kurniati; Sugiarto, Sigit (PATTIMURA UNIVERSITY, 2023)
Ebola Virus Disease (EVD) is an infectious disease with a high mortality rate which is caused by the virus from the family of Filoviridae, genus of Ebolavirus. Therefore, this research works on the developing model of Ebola disease spread with SLSHVEQIHR type. The purpose of this study is to analyze the spread of Ebola disease with the treatments, which are quarantine and vaccination. Then determine the equilibrium point and basic reproduction number (R0). There are two equilibrium points, the disease free equilibrium point and the endemic equilibrium point. The analysis results in the model show that if R0<1 than the disease free equilibrium point is locally asymptotically stable. If R0>1 than the endemic equilibrium point is locally assymptotically stable. Numerical simulations are performed to show the population dynamics when R0<1and R0>1.